Growth of cosmetic procedures in millennials: A 4.5‐year clinical review. (23rd October 2020) - Wang, Jordan V.; Akintilo, Lisa; Geronemus, Roy G.
Abstract: This commentary examines the rise of cosmetic procedures in millennials. With the increasing popularity of aesthetic treatments and the growing share of patients who are millennials, it is important for physicians to understand the current trends, which can offer insights to better forecast patient demand and optimize practice management. Although it has been anecdotally reported that the popularity of cosmetic procedures has increased with millennials, available data on consumer behavior is limited. Our data fills this gap in the literature by examining the patterns of cosmetic procedures in millennials and discussing reasons for these findings. Our data proves an overall upward trend and also breaks down these trends for various individual procedures. Physicians can utilize this information to optimize marketing strategies for millennials in order to capture greater market share and potentially increase practice revenues.